2010
DOI: 10.1016/j.biopsych.2009.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Sidman Instrumental Avoidance Initially Depends on Lateral and Basal Amygdala and Is Constrained by Central Amygdala-Mediated Pavlovian Processes

Abstract: Background The lateral (LA) and central (CE), but not basal (B), amygdala nuclei are necessary for reactive Pavlovian fear responses such as freezing. The amygdala also plays a key role in the acquisition and expression of active instrumental defensive behaviors, but little is known about the specific roles of amygdala nuclei. Using a Sidman active avoidance (AA) task, we examined the necessity of LA, B, and CE for learning and performance. Pavlovian freezing was simultaneously assessed to examine the contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(174 citation statements)
references
References 77 publications
(90 reference statements)
7
167
0
Order By: Relevance
“…Third, both freezing and active behaviors reached higher levels during tone presentation than during the pre-tone period in all animals, indicating that they were tone-induced (i.e., fear-elicited) behavioral responses. Finally, as previously reported in rats (Lázaro-Muñoz et al, 2010;Vicens-Costa et al, 2011), we were able to measure the relationship between the type of coping adopted by individual mice in fear conditioning and active avoidance performances. Altogether, these observations indicate that passive or active fear coping strategies likely represent individual behavioral traits maintained over different experimental conditions.…”
Section: Conditioned Fear Responding Is Influenced By Individual Varimentioning
confidence: 85%
See 3 more Smart Citations
“…Third, both freezing and active behaviors reached higher levels during tone presentation than during the pre-tone period in all animals, indicating that they were tone-induced (i.e., fear-elicited) behavioral responses. Finally, as previously reported in rats (Lázaro-Muñoz et al, 2010;Vicens-Costa et al, 2011), we were able to measure the relationship between the type of coping adopted by individual mice in fear conditioning and active avoidance performances. Altogether, these observations indicate that passive or active fear coping strategies likely represent individual behavioral traits maintained over different experimental conditions.…”
Section: Conditioned Fear Responding Is Influenced By Individual Varimentioning
confidence: 85%
“…tioning were those performing the poorer in active avoidance learning (Lázaro-Muñoz et al, 2010;Vicens-Costa et al, 2011). Previously fear-conditioned mice were submitted to one active avoidance session.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal studies have reported differential distributions of the serotonin transporter protein (Rourke and Fudge, 2006) as well as serotonin-1A and other receptors (Pazos et al, 1987) across these subnuclei, which may underlie variation in treatment effects on amygdala firing. Damaging neurons of the central, basal, and lateral nuclei yields different mediation of fear-related behaviors in animals (Lázaro-Muñoz et al, 2010). Pharmacological studies have shown that the BLA and central amygdala, in particular, have distinct roles in the anxiolytic effect of benzodiazepines (Green and Vale, 1992).…”
Section: Amygdala Subregions In Anxiolysismentioning
confidence: 99%